Interspeech 2017 2017
DOI: 10.21437/interspeech.2017-876
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Phonetic Investigation of Alphabetic Words in Mandarin Chinese

Abstract: Chinese words written partly or fully in roman letters have gained popularity in Mandarin Chinese in the last few decades and an appendix of such Mandarin Alphabetical Words (MAWs) is included in the authoritative dictionary of Standard Mandarin. However, no transcription of MAWs has been provided because it is not clear whether we should keep the original English pronunciation or transcribe MAWs with Mandarin Pinyin system. This study aims to investigate the phonetic adaptation of several most frequent MAWs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…In a Chinese context and under the circumstance that codeswitching is restricted to the word/phrase level, I postulate that such language alternation can be referred to as alphabetic words. Defined as fully or partially romanised Chinese words, Chinese alphabetic words may either contain complete foreign morphemes or take a form of acronyms of Pinyin, the official romanisation system for standard Mandarin adopted in Mainland China (Ding et al, 2017;Hou & Teng, 2016;Su & Wu, 2013). The former category can be exemplified by alphabetic words such as 'hold住' hold zhu ('to hang in there'), while the latter can be exemplified by lg that stands for 老公 laogong ('hubby').…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In a Chinese context and under the circumstance that codeswitching is restricted to the word/phrase level, I postulate that such language alternation can be referred to as alphabetic words. Defined as fully or partially romanised Chinese words, Chinese alphabetic words may either contain complete foreign morphemes or take a form of acronyms of Pinyin, the official romanisation system for standard Mandarin adopted in Mainland China (Ding et al, 2017;Hou & Teng, 2016;Su & Wu, 2013). The former category can be exemplified by alphabetic words such as 'hold住' hold zhu ('to hang in there'), while the latter can be exemplified by lg that stands for 老公 laogong ('hubby').…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The term "lettered words" or "alphabetic words" covers a multitude of sins in the literature and thus is clearly in need of careful and structured analysis. As mentioned above, previous research (Cook 2014;Ding et al 2017;Huang and Liu 黄居仁,刘洪超 2017) has demonstrated that one fundamental distinction that needs to be made is between alphabetic words that are borrowed directly from a European language and those that are coined by native speakers of Modern Standard Chinese. Within each of these two major groups, further subcategorization is also necessary.…”
Section: Classification Of Various Types Of Loansmentioning
confidence: 99%
“…Speakers of any language are perfectly capable of expanding the lexicon of their mother tongue without necessarily having recourse to linguistic elements adopted from other languages. In the case of Modern Standard Chinese, it has been observed that even new words containing Latin letters (so-called "lettered" or "alphabetic words") should not necessarily be analyzed as loanwords since they are sometimes novel creations on the part of Chinese speakers (Cook 2014;Ding et al 2017;Huang and Liu 黄居仁,刘洪超 2017). Cook (2014) isolates three types of Modern Standard Chinese neologisms using Latin letters that are nevertheless deemed to be examples of lexical coinages rather than lexical borrowing; according to the classification system proposed in that study these include novel English expressions (e.g., love hotel), initialisms of Chinese (e.g., RMB; LKK) and Chinese initialisms of English (e.g., GF 'girlfriend'; BF 'boyfriend').…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have tried to resolve the learning challenges from different perspectives. They include steps to overcome anxiety [39,40], motivation to increase performance [41,42], better learning strategies [43][44][45], improvised speaking methods [40,46], and improving intonation perception [47]. Some studies have also investigated the difficulties experienced by learners in technology-aided learning [46,48,49].…”
Section: Literature Reviewmentioning
confidence: 99%